Banking system development, small businesses and minority lending in Nigeria. (4th October 2010) - Ezeoha, Abel E.; Amaeshi, Kenneth
Improving the flow of investible finance to small businesses remains the main thrust of financial system reforms in most developing economies. At the same time, there are conflicting claims on how banking development, necessitated by financial system reforms, impacts on financing of small businesses. Using a co-integration and vector auto regression techniques, with quarterly time-series data spanning from 1970 to 2005, this study examines the long-run relationship between banking development and minority lending in Nigeria. It finds that the kind of structural changes that characterised banking development in Nigeria has negatively affected minority lending; and that flow of credits to small businesses may have largely been explained by prevailing high interest rates and inflation rates. An important implication of this result is that policy efforts to influence the direction of bank credits through some structural policy measures focusing on banking consolidation have not worked in favour of minority businesses.